Literature Review : Peran Modifikasi Epigenetik Dalam Pengembangan Penyakit Diabetes - Windiyani, Intan Poespita; Billy Only Patrick Jonson; Sally Khoirunisa; Galuh Ismayanti (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the Role of Epigenetic Modification in the Development of Diabetes Disease, referring to 11 journals sourced from national and international publications. Using the literature review method. Based on the results obtained, Epigenetic Modification plays an important role in the sustainability of diabetes sufferers, where a person's lifestyle, diet and positive activities can help prevent the severity of diabetes from further damaging a person's body and help change gene expression and produce better blood sugar regulation, increase insulin sensitivity, and fight inflammation and oxidative stress that are often associated with diabetes, and help reduce the risk of this disease affecting offspring and the next generation.